2022
DOI: 10.1097/rlu.0000000000004127
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Potential of Postoperative 18F-Fluorocholine PET/CT in Patients With High-Grade Glioma. Clinical Validation of FuMeGA Postoperative PET Criteria

Abstract: ObjectiveThe aim of this study was to assess the prognostic performance of postoperative 18F-fluorocholine PET/CT in patients with high-grade glioma (HGG).MethodsPatients with HGG who underwent preoperative and postoperative 18F-fluorocholine PET/CT were prospectively enrolled in the study. Postoperative MRI was classified as complete versus incomplete resection. Postoperative 18F-fluorocholine PET/CT was classified as negative (complete) or positive for metabolic residual tumor (incomplete resection) using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
(105 reference statements)
0
1
0
Order By: Relevance
“…The authors found that postoperative positive [ 18 F]Fluorocholine PET/CT localizations correlated with the sites of tumor recurrence. Furthermore, on preoperative PET/CT, they observed that lesions with higher tracer uptake were followed by higher metabolic residual lesions after surgery [ 48 ].…”
Section: Research Strategy Resultsmentioning
confidence: 99%
“…The authors found that postoperative positive [ 18 F]Fluorocholine PET/CT localizations correlated with the sites of tumor recurrence. Furthermore, on preoperative PET/CT, they observed that lesions with higher tracer uptake were followed by higher metabolic residual lesions after surgery [ 48 ].…”
Section: Research Strategy Resultsmentioning
confidence: 99%